Grape seed pro‐anthocyanidins ameliorates radiation‐induced lung injury. Issue 7 (24th April 2014) - Huang, Yijuan; Liu, Wen; Liu, Hu; Yang, Yanyong; Cui, Jianguo; Zhang, Pei; Zhao, Hainan; He, Feng; Cheng, Ying; Ni, Jin; Cai, Jianming; Li, Bailong; et al.
Abstract Radiation‐induced lung injury (RILI) is a potentially fatal and dose‐limiting complication of thoracic radiotherapy. This study was to investigate the protective effects of grape seed pro‐anthocyanidins (GSPs), an efficient antioxidant and anti‐carcinogenic agent, on RILI. In our study, it was demonstrated that acute and late RILI was ameliorated after GSPs treatment possibly through suppressing TGF‐β1/Smad3/Snail signalling pathway and modulating the levels of cytokines (interferon‐γ, IL‐4 and IL‐13) derived from Th1/Th2 cells. In addition, a sustained high level of PGE2 was also maintained by GSPs treatment to limited fibroblast functions. As shown by electron spin resonance spectrometry, GSPs could scavenge hydroxyl radical (OH) in a dose‐dependent manner, which might account for the mitigation of lipid peroxidation and consequent apoptosis of lung cells. In vitro, GSPs radiosensitized lung cancer cell A549 while mitigating radiation injury on normal alveolar epithelial cell RLE‐6TN. In conclusion, the results showed that GSPs protects mice from RILI through scavenging free radicals and modulating RILI‐associated cytokines, suggesting GSPs as a novel protective agent in RILI.